Sistem Monitoring Dan Kontrol Berbasis Internet Of Things Pada Prototypesmart Portable Biomass Powerplant - Muzhaffar, Raihan Faishal; Putra, I Wayan Sri Atma; Brahmananda, A.A. Ngurah Agung Satria; Sudarma, Made; Manuaba, Ida Bagus Gede (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
The use of Internet of Things technology can be implemented in various aspects, one of which is the field of energy generation. The generation of electrical energy, especially biomass fuel, can be one way to achieve more environmentally friendly energy generation. Design prototype smart portable biomass powerplant includes monitoring and control of the generating system. The monitoring and control system is designed to be able to run automatically integrated with the Internet of Things system. To increase the ease of use of the tool, the system is connected in real-time with the internet. Data acquisition with sensors connected to the controller is carried out to observe the condition of the combustion chamber, turbine and generator components. The results of this data acquisition can then be monitored in real-time on a platform that can be done remotely. The control process on the prototype includes protection measures on the device in case of fault so as to provide further damage prevention measures and can be done wirelessly using the same system. Prototype testing results using Arduino mega2560 controller and ACS712 current sensor, voltage sensor, MQ-2 gas sensor and esp32 cam were found to be able to work well and monitor both the condition of the combustion chamber, the power generated by the generator to biomass combustion levels. Then the test also proved to be able to provide remote process control to protect the tool from overheating, overcurrent protection and excessive incomplete combustion process.